Preoperative cephalic vein diameter and diabetes do not limit the choice of wrist radio-cephalic arteriovenous fistula. Issue 3 (May 2020) - Hou, Guocun; Yan, Yonghong; Li, Guangyi; Hou, Yi; Sun, Xiuli; Yin, Na; Feng, Guozhen
Aim: To identify predictors that affect initial maturation of new wrist radio-cephalic arteriovenous fistula and evaluate the clinical effects of the ipsilateral mid-forearm radio-cephalic arteriovenous fistulas creation in the event of first wrist radio-cephalic arteriovenous fistula failure. Methods: We performed a retrospective review of all patients who underwent first wrist radio-cephalic arteriovenous fistula creation between September 2016 and May 2018. Currently, we prefer to re-create an ipsilateral mid-forearm radio-cephalic arteriovenous fistula when the first wrist radio-cephalic arteriovenous fistula fails. Predictors of successful radio-cephalic arteriovenous fistulas were identified using univariate and multivariate analyses. Kaplan–Meier survival analysis and log-rank test were used to calculate successful radio-cephalic arteriovenous fistula rates. Results: Univariate analysis showed that predictive factors for successful wrist radio-cephalic arteriovenous fistula include larger preoperative cephalic vein diameter ( p  = 0.001) and non-diabetic kidney disease ( p  = 0.007). Multivariate binary logistic regression analysis revealed cephalic vein diameter ⩾2 mm (odds ratio = 4.55, 95% confidence interval = (1.49–13.92), p  = 0.008) and non-diabetic kidney disease (odds ratio = 4.22, 95% confidence interval = (1.38–12.88), p  = 0.011) to be independent predictors for successful radio-cephalic arteriovenous fistula. We re-created ipsilateral mid-forearm radio-cephalic arteriovenous fistulas in 15 patients among the 21 failed wrist radio-cephalic arteriovenous fistulas; all these arteriovenous fistulas maintained clinical maturation following up for 1–2 years. Conclusion: Small cephalic vein diameter (<2 mm) and diabetes were independent risk factors for failed wrist radio-cephalic arteriovenous fistulas, but this risk could be overcome by aggressive ipsilateral mid-forearm radio-cephalic arteriovenous fistula to address a failed first attempt. Cephalic vein diameter is more important during the maturation stage, and once maturation has occurred, diabetes has an additive role in determining the patency of wrist radio-cephalic arteriovenous fistula. The "wrist RCAVF first, ipsilateral mid-forearm RCAVF second" strategy is the most clinically significant message of our study.